- TINJAUAN LITERATUR PARAMETER SPESIFIK DAN NON-SPESIFIK PADA SIMPLISIA DAN EKSTRAK BUNGA SEBAGAI BAHAN BAKU HERBAL TERSTANDAR - Maria Indriati Ose; Lulu Hikmah Fauziah; Mahardika Shaib Prayoga; Cesarianti Puteri Dwi Hatmoko; Yonathan Tri Atmodjo Reubun (Jurnal Ayurveda Medistra, 2026)
Flowers are a source of secondary metabolites that can be used as raw materials for herbal medicines. The standardization of crude drug materials and flower extracts using specific and non-specific parameters is essential to ensure their quality, safety, and efficacy. This study aims to review the specific and non-specific parameters of ten types of flowers, namely gemitir, soka, rosella, clove, kecombrang, tapak darah, pucuk merah, telang, matahari, and kembang bulan. The analyzed parameters include organoleptic properties, water and ethanol extract yields, phytochemical tests, identification of active compounds via TLC and GC-MS, as well as moisture content, ash content, and percentage of damage due to heating. The results showed that seven flowers (gemitir, rosela, kecombrang, tapak darah, pucuk merah, matahari, and kembang bulan) met most of the quality parameters. Moisture content was generally <10%, but the cengkeh flower had high moisture content (18.9%) and the kembang bulan flower had a drying loss exceeding the limit (13.64%). The highest water-soluble extract content was found in gemitir (37.34%) and tapak darah (30.2%), while soka (20.7%) and telang (8.5%) were below the standard. All flowers contain flavonoids, with the best identification of active compounds found in rosella (quercetin 7.02%) and moonflower (GC-MS results). Overall, most flowers can be used as standardized herbal raw materials, but soka, clove, and telang flowers still require improvements in the processing.